2023
DOI: 10.3748/wjg.v29.i2.257
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and liver injury: An ongoing challenge

Abstract: The new coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was identified in December 2019, in Wuhan, China. The virus was rapidly spread worldwide, causing coronavirus disease 2019 (COVID-19) pandemic. Although COVID-19 is presented, usually, with typical respiratory symptoms ( i.e. , dyspnea, cough) and fever, extrapulmonary manifestations are also encountered. Liver injury is a common feature in patients with COVID-19 and ranges from mild and temporary elevation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 121 publications
(152 reference statements)
1
15
0
Order By: Relevance
“…Liver injury is a common feature in COVID-19 patients and is associated with disease severity and prognosis usually exhibiting mild elevation of the aminotransferases <5 times above the upper limit of normal (ULN), only. 10 In such cases, liver injury was transient with liver function parameters returning to normal within 2-3 weeks. 11 In contrast, increased GGT and/or ALP are less common features, mainly observed in later disease stages.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Liver injury is a common feature in COVID-19 patients and is associated with disease severity and prognosis usually exhibiting mild elevation of the aminotransferases <5 times above the upper limit of normal (ULN), only. 10 In such cases, liver injury was transient with liver function parameters returning to normal within 2-3 weeks. 11 In contrast, increased GGT and/or ALP are less common features, mainly observed in later disease stages.…”
Section: Discussionmentioning
confidence: 99%
“…11 In contrast, increased GGT and/or ALP are less common features, mainly observed in later disease stages. 10 Severe hepatotoxicity (i.e., aminotransferases elevation >20 times ULN) has been reported to affect 2% of hospitalized COVID-19 patients, with acute liver failure being an extremely rare event. 17 A recent study including 158 hospitalized patients showed, that the incidence of abnormal liver function tests (LFTs) was significantly higher in severe than in nonsevere COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations